The Depiction of Hegemony Created and Developed by the Group of The Pigs in Orwell’s Animal Farm - Arifriarni, Kenanga Fajar (Jurnal Bahasa, Sastra, dan Studi Amerika, 2021)
Power is one of the most wanted things in this world. Many people compete with each other for power. Sometimes, some of them use their cunning to accomplish their desire for power. When they succeed to get it, they will do everything to maintain their positions. This research explores those kinds of issues portrayed in George Orwell’s novel entitled Animal Farm (1945). Furthermore, the research focuses on the process of how hegemony takes place in Animal Farm. Antonio Gramsci’s theory about hegemony is used to analyze the data. The research finds out that from the beginning to the end of the story, Orwell’s Animal Farm shows the system of hegemony created and developed by the pigs’ group. Old Major’s speech made the animals realized their real condition and triggered the animals to rebel against their master, Mr. Jones. Even though their rebellion succeeded to expel Mr. Jones and his men from the farm, it emerged the new supremacy of the pigs. Snowball only used consent to rule the animals. On the other hand, Napoleon used the combination of consent and coercion to rule the animals.